Serum metabolic profiling in diabetic kidney disease patients using ultra-high performance liquid chromatography-tandem mass spectrometry - Bin Zhang; Chunmei Dai; Jiuyi Jiang; Jun Wang; Yuwei Yang; Jiafu Feng (Diabetology & Metabolic Syndrome)
Abstract Background Diabetic kidney disease (DKD) remains one of the leading causes of end-stage renal failure. The currently available diagnostic and classification markers, such as the urinary albumin-to-creatinine ratio and estimated glomerular filtration rate, demonstrate inadequate precision in forecasting the onset and progression of DKD. This study aims to investigate the serum metabolic profile of patients with DKD, with the objective of identifying reliable biomarkers that can enhance the prediction of the transition from diabetes mellitus (DM) to DKD and distinguishing DKD from nondiabetic kidney disease (NDKD). Methods Untargeted metabolomic analysis was performed on serum samples obtained from 53 DKD patients, 54 NDKD patients, 59 individuals diagnosed with simple diabetes mellitus (SDM), and 56 healthy controls utilizing ultra-high performance liquid chromatography-tandem mass spectrometry. Differential metabolites among the groups were identified, metabolic pathways were investigated, and the diagnostic efficacy of selected metabolites was evaluated. Results The metabolic enrichment pathways shared between DKD and NDKD encompassed glycerophospholipid metabolism, glycerolipid metabolism, and tryptophan metabolism. In contrast, pyrimidine metabolism and arginine biosynthesis were uniquely enriched in DKD. Compared to the NDKD group, significantly elevated levels of phosphatidylglycerol (PG, 14:0) and D-Maltose were observed in DKD patients. Additionally, in comparison to the SDM group, the DKD group exhibited significant increases in lysophosphatidic acid (LPA, 16:3), LPA (18:5), LPA (22:5), phosphatidic acid (PA, 18:3), PG (26:4), L-Glutamine, Uridine, Cytidine, Formyl-N-acetyl-5-methoxykynurenamine, 2-Oxoadipate, Thymidine, L-Citrulline, and 5-Hydroxy-L-tryptophan, while PG (28:4) levels were markedly reduced. Among these, Uridine, Cytidine, Thymidine, and L-Citrulline were associated with pyrimidine metabolism, whereas L-Glutamine and L-Citrulline participated in the arginine biosynthesis pathway. Furthermore, the differential metabolites exhibited varying degrees of correlation with renal function indicators in DKD patients. Conclusions PG (14:0) and D-Maltose may help distinguish DKD from NDKD, while L-Glutamine, Uridine, Cytidine, Thymidine, and L-Citrulline are linked to the progression from DM to DKD. Larger studies are needed to validate these findings and assess their diagnostic and causal significance.